Mycobacterium Abscessus – Diagnostic and Therapeutic Frontiers in Infection Management - Masiarova, Simona; Matus Dohal; Porvaznik, Igor; Solovic, Ivan; Mokry, Juraj (Acta Medica Martiniana, 2023)
Mycobacterium (M.) abscessus, a highly pathogenic non-tuberculous mycobacterium, is responsible for several clinical manifestations. A very frequent occurrence is proven in patient with various lung diseases. Furthermore, it can result in complications such as skin and soft tissue diseases, central nervous system infections, bacteremia, eye infections, and others. M. abscessus is a clinical contraindication in cystic fibrosis patients awaiting a lung transplant, as it can exacerbate disease progression. Its pathogenicity and the emergence of resistance are influenced by factors including the composition of the cell envelope, rough and smooth M. abscessus morphotypes, efflux pumps, antibiotic-modifying/inactivating enzymes, and genetic polymorphisms in target genes. Management of the infection requires multicomponent therapy due to the high level of resistance. The following antibiotics are recommended according to the guidelines from the year 2017: amikacin, tigecycline, and imipenem with a macrolide. In order to properly manage patients with M. abscessus infection, correct identification of the subspecies as well as determination of resistance is essential. To achieve this goal, molecular-genetic techniques, such as whole-genome sequencing, are becoming increasingly favored in modern clinical practice. In this review, we provide up-to-date information on the issue of infections caused by non-tuberculous M. abscessus. We focus on its characteristics, possible infectious diseases, cystic fibrosis, and resistance, as well as the benefits of whole-genome sequencing.